Sorghum surpasses wheat as a feed grain for broiler chickens following dietary crude protein reductions - Mengzhu Wang; Mehdi Toghyani; Shemil P. Macelline; Andreas Lemme; Andrew J. Holmes; Peter H. Selle; Sonia Y. Liu (Journal of Animal Science and Biotechnology)
Abstract Background Wheat and, to a lesser extent, sorghum are the dominant feed grains in Australian chicken-meat production. There is considerable local interest in the development of reduced-crude protein (CP) broiler diets in part because this would decrease the need to import soybean meal into the country. Maize is rarely included in Australian broiler diets, but birds appear better able to accommodate dietary CP reductions with maize than with wheat-based diets. Sorghum is more similar to maize than wheat and for this reason wheat- and sorghum-based diets, with standard and reduced-CP concentrations, were evaluated in broiler chickens in a direct comparison. Results Reducing dietary CP from 205 to 175 g/kg CP did not statistically influence weight gain and FCR in broilers offered sorghum-based diets from 14 to 35 d post-hatch. In contrast, the 30 g/kg CP reduction compromised weight gain by 10.1% (1,964 versus 2,187 g/bird) and FCR by 9.68% (1.575 versus 1.436), in broilers offered wheat-based diets. Consequently, treatment interactions (P < 0.001) were observed for dietary CP levels grain type for both weight gain and FCR. Another treatment interaction (P < 0.001) was observed for starch digestibility coefficients in the distal jejunum. Birds offered 205 g/kg CP, wheat-based diets had superior starch digestibility by 11.6% (0.914 versus 0.819), but sorghum supported superior starch digestibility by 9.70% (0.837 versus 0.763) in the context of 175 g/kg CP diets. Conclusions Under the condition of thid study, broiler chickens offered sorghum-based diets had a greater capacity to accommodate dietary CP reductions than their counterparts offered wheat-based diets. This study confirmed that wheat-based diets are not conducive to CP reductions, but the causal factors have yet to be identified precisely.